POLYSEMY IN TEACHING NEW VOCABULARY UNITS - Najmiddinova , Aziza Shuhratovna; Rustamova, Adash Eshankulovna (INTERNATIONAL CONFERENCES, 2023)
In this article, a comparative typological analysis of the new lexical units is carried out, while studying the specific characteristics of them. Also, the phenomenon of polysemy and homonymy in new lexical units in considered.